Comparative Analysis of Profitability of Partnership Pattern of People's Sugarcane Credit (TRK) with Independent People's Sugarcane (TRM) (Case Study at PT. PG Rajawali II Sindanglaut Unit) - Muhammad Fazri; Iftitakhatur Rizqiyah; Bella Sukmarini; Akhmad Jaeroni; Tety Suciaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to compare the profitability of the partnership pattern of People’s Sugarcane Credit (TRK) and Independent People’s Sugarcane (TRM) in PT. PG Rajawali II Sindanglaut Unit. This research method uses descriptive quantitative with profitability analysis, differential test, and multiple linear regression. The sample of this study is 90 farmers, including 30 TRK and 60 TRM. The result of this study is that there are differences in working capital financing mechanisms between TRK and TRM. The profitability analysis showed a significant difference with the profitability of TRM of (15.84%) higher than the TRK of (12.15%). Multiple linear regression analysis states that the production variable and the KUR loan variable have a significant effect on profitability, with the production variable being the most significant factor on profitability.